Transient Overexpression of Gremlin Results in Epithelial Activation and Reversible Fibrosis in Rat Lungs - Farkas, Laszlo (American Thoracic Society, 2011)
Idiopathic pulmonary fibrosis (IPF) is a progressive fibrotic disease of the lung parenchyma, without curative treatment. Gremlin is a bone morphogenic protein (BMP) antagonist, its expression being increased in IPF lungs. It has been implicated in promoting myofibroblast accumulation, likely through inhibited fibroblast apoptosis and epithelial-to-mesenchymal transition. In the current study, we examined the effects of selective adenovirus-mediated overexpression of Gremlin in rat lungs. We show that transient Gremlin overexpression results in activation of alveolar epithelial cells with proliferation and apoptosis, as well as partly reversible lung fibrosis. We found myofibroblasts arranged in fibroblastic foci. Fibroblast proliferation occurred delayed as compared with epithelial changes. Fibrotic pathology significantly declined after Day 14, the reversal being associated with an increase of the epithelium-protective element, fibroblast growth factor (FGF)–10. Our data indicate that Gremlin-mediated BMP inhibition results in activation of epithelial cells and transient fibrosis, but also induction of epithelium-protective FGF10. A Gremlin–BMP–FGF10 loop may explain these results, and demonstrate that the interactions between different factors are quite complex in fibrotic lung disease. Increased Gremlin expression in human IPF tissue may be an expression of continuing epithelial injury, and Gremlin may be part of activated repair mechanisms.